Six sigma for scrap cost reduction in remanufacturing industry - Mat Kiah, Missjuliana (2015)
This project entails the adoption of Six Sigma Methodology in remanufacturing industry. The improvement project is carried out at a service and repair company for electronic product. Six Sigma is a set of quality management tools and strategies, including statistical methods used for process improvement by identifying and eliminating the causes of defects and reducing variability occurs in manufacturing and other businesses process. The Six Sigma DMAIC methodology consists of five phases which are Define (D), Measure (M), Analyse (A), Improve (I), and Control (C) respectively. This case study focuses on implementing Six Sigma methodologies into the motherboard repair process in to identify and minimize the variation exists in the process and subsequently reducing the associated scrap cost. As known, the original assembly process of motherboard is comparatively straightforward. However, the repair process of malfunction motherboard which requires troubleshooting of problem and replacement of electronic devices can be much more complicated and often end-up scrapping the whole set of motherboard itself. Realizing this great challenge, the DMAIC tools are mounted in this study to solve the underlying problem stated. The objective of the project is to reduce the overall scrap rate and to increase the sigma level of the motherboard repair process. The existing scrap rate is 45.89% and process sigma level is 1.84s. It is proven that the method and tools chosen have successfully reduced the scrap rate to 18.60% and increased the process sigma level to 2.46s in three months period after the improvement took place. This result indicates that Six Sigma methodology is also applicable in remanufacturing industry as good as in forward manufacturing industry.